2012
DOI: 10.1177/0897190012442218
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Usage of Printed and Electronic Drug References and Patient Medication Records in Community Pharmacies in Malaysia

Abstract: This study aimed to determine the availability and usage of printed and electronic references and Patient Medication Record in community pharmacy. It was conducted for over 3 months from 15 January to 30 April 2007. Ninety-three pharmacies participated. Structured questionnaires were mailed to community pharmacies. Six weeks later a reminder was sent to all non responders, who were given another six weeks to return the completed questionnaire. Outcomes were analyzed using descriptive statistics and chi-square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Also, Individual characteristics , which includes factors like insufficient knowledge regarding sources and a lack of searching skills , ranked first as barriers for pharmacists but last for physicians. These barriers were frequently mentioned in relation to the Internet (Burgess et al, 2004; Hennigen et al, 2009; Usir et al, 2012; Wong et al, 2009; Zehnder et al, 2004), possibly contributing to their low usage. A systematic review by Maclure and Stewart (2016) found that pharmacists want or need more digital literacy training, however recommendations from individual studies lack baseline data and are not current, quantifiable, measurable or specific.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Individual characteristics , which includes factors like insufficient knowledge regarding sources and a lack of searching skills , ranked first as barriers for pharmacists but last for physicians. These barriers were frequently mentioned in relation to the Internet (Burgess et al, 2004; Hennigen et al, 2009; Usir et al, 2012; Wong et al, 2009; Zehnder et al, 2004), possibly contributing to their low usage. A systematic review by Maclure and Stewart (2016) found that pharmacists want or need more digital literacy training, however recommendations from individual studies lack baseline data and are not current, quantifiable, measurable or specific.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because Kostagiolas et al studied hospital pharmacists but half of the articles on pharmacists included in this review studied community pharmacists solely. The lack of Internet access by community pharmacists has been suggested by several studies (Al-Farsi et al, 2014;Burgess et al, 2004;McCaw et al, 2008;Usir et al, 2012).…”
Section: Drug Information Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Only one of the studies described the utility of technology in patient records management. 107 In other studies, telehealth was employed in type 2 diabetic patients 96 and during the COVID-19 pandemic for patients with epilepsy (PWE). 60 The use of complementary and alternative medicine (CAM) for atopic dermatitis was described in a South African study.…”
Section: Search Strategymentioning
confidence: 99%
“…36,43,45,53,54,57,65,71,79 Provider-initiated interventions such as task-shifting, the use of technology and the rearrangement of physical structures in the pharmacy to improve work ow and ergonomics have been recommended by other studies. 33,64,86,88,107,117 Providing mandatory continuous professional development by regulatory and professional bodies to community help keep abreast of the current issues, as related to practice, was advocated in the other included studies. 32,36,40,40,50,56,70,71,73,82,84,86,94,101,102,104,105,112,114,118 Only one study mentioned the integration of CAM into the undergraduate pharmacy curriculum.…”
Section: Recommendations To Overcome These Barriersmentioning
confidence: 99%